TEORI SELF CARE DARI OREM DAN PENDEKATAN DALAM PRAKTEK KEPERAWATAN - Abi Muhlisin; Irdawati Irdawati (Jurnal Berita Ilmu Keperawatan, 2009)
Nursing care service given by a nurse hardly influences quality of treatment upbringing which will be received by client. Therefore to be able to give treatment upbringing that is with quality hence nurse need to develop science and practice of treatment one of them is through usage of conceptual model in upbringing giving. Various conceptual models of treatment which has been developed by the experts, one of them is is Self Care Deficit by Dorothea Orem. Principal focus from this conceptual model is ability of someone to take care of their/his self self-supportingly causing is reached ability to maintain its(the health and prosperity. This theory also is a base for nurse in self-supporting of client according to level of its(the dependency do not place client in dependent position, because according to Orem, as of care ldf do not process intuition but is a my prila which can be studied.